AN ANALYSIS OF THE FORMATION AND MEANING OF INTERNET SLANG IN ONLINE COMMUNICATION (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research investigates one emerging linguistic phenomenon is internet slang, which allows users to communicate efficiently while expressing creativity and social identity in online communities. This study aims to identify the word formation processes used in internet slang and to analyze the social and linguistic factors influencing its usage and meaning among internet users. This research applied a descriptive qualitative method. Data consisted of internet slang expressions collected from Instagram, TikTok, and Twitter through observation and documentation of posts, captions, and comment sections. The analysis was based on the morphological theory of word formation proposed by George Yule (2010), including acronym, clipping, blending, compounding, derivation, and borrowing. Data analysis followed the interactive model of Matthew Miles and Huberman consisting of data reduction, data display, and conclusion drawing. The findings show that internet slang is mainly formed through acronym, clipping, blending, and compounding. These processes demonstrate the linguistic creativity of internet users in creating or modifying words for faster and more expressive communication. Its usage is also influenced by social and linguistic factors such as group identity, humor, emotional expression, social interaction, and communication efficiency. In conclusion, internet slang reflects the dynamic development of language influenced by technological advancement and social interaction in digital communication.